2001
DOI: 10.1590/s0103-84782001000600017
|View full text |Cite
|
Sign up to set email alerts
|

Redução fechada e fixação esquelética externa tipo II para o tratamento de fraturas de tibiotarso em pombos domésticos (Columba livia)

Abstract: A redução fechada e o fixador esquelético externo tipo II foram avaliados para o tratamento de fraturas de tibiotarso em pombos domésticos (Columba livia). Foram utilizadas doze aves adultas. Os pombos foram anestesiados com a associação de xilazina e cetamina e, em seguida, foi realizada fratura do tibiotarso direito através de pressão digital sobre a diáfise do membro. Quatro pinos de Kirschner, dois proximais e dois distais ao foco da fratura, foram inseridos através de ambas as corticais ósseas e, após red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 3 publications
(1 reference statement)
2
2
0
5
Order By: Relevance
“…The antibiotic used (enrofloxacin) and the dose calculated by allometric extrapolation were efficient, avoiding postoperative infections, as observed by other authors (Leotte et al, 2004;Alievi et al, 2001;Gaiga & Schossler, 2002;Dalmolin et al, 2007;Rocha et al, 2009). Some other studies have reported positive use of ampicillin (Alievi et al, 2008).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…The antibiotic used (enrofloxacin) and the dose calculated by allometric extrapolation were efficient, avoiding postoperative infections, as observed by other authors (Leotte et al, 2004;Alievi et al, 2001;Gaiga & Schossler, 2002;Dalmolin et al, 2007;Rocha et al, 2009). Some other studies have reported positive use of ampicillin (Alievi et al, 2008).…”
Section: Resultssupporting
confidence: 64%
“…During this period, animal had use of limb, which meets citations that radiographic consolidation happens later than clinical use of the limb (Williams et al, 1987;Wissman, 1999;Alievi et al, 2001). This supports findings that external fixators allow adequate movement of joints proximal and distal to the fracture, avoiding complications of non-use of the limb during bone healing (Pead & Cardmichael, 1989;Dalmolin et al, 2007).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Segundo Alievi et al (2001) as aves apresentam boa adaptação ao aparelho de fixação esquelética externa o quê possibilita sua utilização por estes animais, sem prejuízos funcionais.…”
Section: Fixadores Externos Em Avesunclassified
“…Porém no trabalho de Alievi et al (2001) as aves apresentaram utilização normal do membro, e eles acreditam que isto ocorreu devido à grande habilidade que as aves possuem para compensar este problema.…”
Section: Fraturas Umeraisunclassified